(untitled) (Scientific journal of the Fergana State University, 2023)
The article touches upon the issues of forming the cultural outlook of learners and the role of a teacher in this process. Furthermore, the pedagogical requirements and capabilities, related to forming the cultural outlook of learners, have been analyzed